2013 IEEE International Conference on Mechatronics and Automation 2013
DOI: 10.1109/icma.2013.6618105
|View full text |Cite
|
Sign up to set email alerts
|

Hand-eye 3D pose estimation for a drawing robot

Abstract: In order to draw pictures on a plane, it is important for a robot arm to know the pose of the end-effecter relative to the world frame which is settled on the workplace. Visual servoing is frequently used in the hand-eye configuration of robot arms. However, 3D pose is preferred for a drawing robot. It is not only required to obtain the three dimensional position of the end effecter so that the pen can touch the paper without drilling a hole, but also required to get the direction so that the pen is always per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Sultan M.S. [28] combines robot kinematics, vision, and force sensors to independently perform hand-eye coordination tasks, and the proposed method accurately determines the camera pose of single-view objects. The corners are indirectly detected from the intersection of lines, and the lines are obtained using RANSAC (Random Sample Consumus) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Sultan M.S. [28] combines robot kinematics, vision, and force sensors to independently perform hand-eye coordination tasks, and the proposed method accurately determines the camera pose of single-view objects. The corners are indirectly detected from the intersection of lines, and the lines are obtained using RANSAC (Random Sample Consumus) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…According to the most rigid objects' feature on the ground with the mutually perpendicular or nearly perpendicular planar structures, Lv et al 12 adopted the normals of planar areas on the target surface to estimate the 3D pose of the target with ladar range image. Sultan et al 13 proposed a monocular camera vision system for a 6-degree of freedom (DOF) drawing robotic arm to estimate 3D pose of the end effecter robustly. Kirac et al 14 had demonstrated an implementation of regression forests for estimation of the articulated 3D pose of the human hand.…”
Section: Introductionmentioning
confidence: 99%
“…Dan Lv et al 2 achieve a 3D pose estimation model for the rigid objects on the ground to recognize the military vehicles automatically. Malik Saad Sultan et al 3 propose a monocular camera vision system for a 6-degree-of-freedom (DOF) drawing robotic arm by estimating the 3D pose of the end effecter robustly. Furkan Kirac et al 4 detect the 3D pose of hand gesture from single frame depth data to realize the humancomputer interaction.…”
Section: Introductionmentioning
confidence: 99%